SYSTEMATIC LITERATURE REVIEW: PENERAPAN K-MEANS CLUSTERING - Albert Putra Pratama; Vita Nurul Fathya; Muhammad Fahrury Romdendine (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study is a systematic literature review on the application of K-Means Clustering in various sectors using the PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analyses) approach. The clustering technique, particularly K-Means, is widely used in big data analysis due to its simplicity and efficiency. Although this method is popular, the main challenges include determining the optimal number of clusters, handling outliers, and computational limitations when applied to large-scale data. This research analyzes sectors that apply K-Means Clustering, such as industry, education, healthcare, and finance. The findings of this study are expected to provide insights into the trends in the use of clustering methods and offer recommendations on the most suitable tools for applying clustering based on data characteristics .